Kochanowicz, Kula, zacofanie. O badaniach wschodnioeuropejskiej peryferii - Sosnowska, Anna (Roczniki Dziejów Społecznych i Gospodarczych, 2015)
Kochanowicz, Kula, backwardness. Regarding the studies of Eastern European peripheries (Summary) The article offers an analysis of the main strands of Jacek Kochanowicz’s research into the backwardness of Eastern Europe. The author attempts to answer the question concerning the extent to which Kochanowicz’s ‘backwardness studies’ built on the research he had carried out earlier under the supervision of Witold Kula. Kochanowicz differed from Kula in his explanation of the economic backwardness of Eastern Europe. Kula, in explaining this phenomenon, stressed the fact that in the sixteenth to eighteenth centuries Eastern Europe relied for its resource bases on the capitalistic centre and that institutional changes occurring in the area in the eighteenth to twentieth centuries were of a hybrid nature. Kochanowicz, by contrast, argued that the backwardness of Eastern Europe originated in the economic (from the sixteenth century on) and cultural (from the nineteenth century) domination of the Polish nobility whose mentality did not favour the growth of entrepreneurial spirit. In addition to the domination of the nobility, the causes of Poland’s backwardness lay in the weakness of Polish towns and of Polish peasantry. However, Kochanowicz continued to draw on the methods used by Kula. Interested in sociology and anthropology, he developed an interdisciplinary approach to economic history, adopting a longue durée perspective and using broad comparisons.